Elucidating the Mechanism of Efficient Eu(III) and Yb(III) Sensitisation from a Re(I) Tetrazolato Triangular Assembly - Wright, P.J.; Pfrunder, M.C.; Etchells, I.M.; Haghighatbin, M.A.; Raiteri, Paolo; Ogden, Mark; Stagni, S.; Hogan, C.F.; Cameron, L.J.; Moore, E.G.; Massi, Max (2024)
The reaction of Re(CO)5Br with deprotonated 1H-(5-(2,2′:6′,2′′-terpyridine)pyrid-2-yl)tetrazole yields a triangular assembly formed by tricarbonyl Re(I) vertices. Photophysical measurements reveal blue-green emission with a maximum at 520 nm, 32 % quantum yield, and 2430 ns long-lived excited state decay lifetime in deaerated dichloromethane solution. Coordination of lanthanoid ions to the terpyridine units red-shifts the emission to 570 nm and also reveals efficient (90 %) and fast sensitisation of both Eu(III) and Yb(III) at room temperature, with a similar rate constant kET on the order of 107 s−1. Efficient sensitisation of Eu(III) from Re(I) is unprecedented, especially when considering the close proximity in energy between the donor and acceptor excited states. On the other hand, comparative measurements at 77 K reveal that energy transfer to Yb(III) is two orders of magnitude slower than that to Eu(III). A two-step mechanism of sensitisation is therefore proposed, whereby the rate-determining step is a thermally activated energy transfer step between the Re(I) centre and the terpyridine functionality, followed by rapid energy transfer to the respective Ln(III) excited states. At 77 K, the direct Re(I) to Eu(III) energy transfer seems to proceed via a ligand-mediated superexchange Dexter-type mechanism.